2000
DOI: 10.1021/je990316q
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Anthracene in Ternary Methyl tert-Butyl Ether + Alcohol + Heptane Solvent Mixtures at 298.15 K

Abstract: Experimental solubilities are reported for anthracene dissolved in ternary methyl tert-butyl ether + 1-propanol + 2,2,4-trimethylpentane, methyl tert-butyl ether + 2-propanol + 2,2,4-trimethylpentane, methyl tert-butyl ether + 1-butanol + 2,2,4-trimethylpentane, methyl tert-butyl ether + 2-butanol + 2,2,4-trimethylpentane, and methyl tert-butyl ether + 2-methyl-1-propanol + 2,2,4-trimethylpentane solvent mixtures at 25°C and atmospheric pressure. Nineteen compositions were studied for each of the five solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The predictive expression for the ternary solvent mixture is a mole fraction average of the logarithmic solute solubilities in the three pure solvents [(x A sat ) B , (x A sat ) C , and (x A sat ) D ] plus a Redlich-Kister summation term for each solvent pair. The documented success [11][12][13][14][15][16] of eq 3 in predicting anthracene solubilities in more than 60 different ternary solvent systems illustrates the need for measured solute solubilities in binary solvent mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…The predictive expression for the ternary solvent mixture is a mole fraction average of the logarithmic solute solubilities in the three pure solvents [(x A sat ) B , (x A sat ) C , and (x A sat ) D ] plus a Redlich-Kister summation term for each solvent pair. The documented success [11][12][13][14][15][16] of eq 3 in predicting anthracene solubilities in more than 60 different ternary solvent systems illustrates the need for measured solute solubilities in binary solvent mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Deng et al . and Pribyla et al. have shown that the S i coefficients determined by regressing experimental anthracene data in binary alkane + alkane, alkane + alcohol, alcohol + alcohol, alcohol + ether, and alkane + ether solvent mixtures allows one to predict anthracene solubilities in ternary alkane + alkane + alcohol, alkane + alcohol + alcohol, and alkane + alcohol + ether solvent mixtures. The predictive expression for the ternary solvent mixture is a mole fraction average of the logarithmic solute solubilities in the three pure solvents [( ) B , ( ) C , and ( ) D ] plus a Redlich−Kister summation term for each solvent pair.…”
Section: Resultsmentioning
confidence: 99%
“…The predictive expression for the ternary solvent mixture is a mole fraction average of the logarithmic solute solubilities in the three pure solvents [(x A sat ) B , (x A sat ) C , and (x A sat ) D ] plus a Redlich-Kister summation term for each solvent pair. The documented success [11][12][13][14][15][16] of eq 4 in predicting anthracene solubilities in more than 60 different ternary solvent systems illustrates the need for measured solute solubilities in binary solvent mixtures.…”
Section: Resultsmentioning
confidence: 99%